(2x - 3)/4 - 3x/2 = 2x-18
Multiply by 4 to remove denominators:
2x - 3 - 2*3x = 4*(2x-18)
2x - 3 - 6x = 8x - 72
12x = 69
x = 69/12 = 5 3/4
2007-06-25 02:58:46
·
answer #1
·
answered by McFate 7
·
0⤊
0⤋
(2x-3)/4 - 3x/2 = 2x -18 => multiply by 4 => 2x-3-6x = 8x-72 then slove for x, x = 69/12 = 23/4
2007-06-25 03:05:32
·
answer #2
·
answered by michael C 1
·
0⤊
0⤋
multiply (3x/2) by 4 to make like denominators =6x/4
subtract both fractions (2x-3)/4 - (6x/4)
(-4x-3)/4= 2x-18
multiply 4 to both sides to get rid of denominator
-4x-3=8x-72
bring x on one side and numbers on other
-12x=-69
x=69/12
x=23/4
ps Julie J
im in 7th grade too...
2007-06-25 03:07:59
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
2x-3/4 - 3x/2 = 2x -18
(2x-3-6x)/4=2x-18
-4x - 3 = 8x - 72
69 = 12x
x = 69/12
= 5.75
2007-06-25 03:00:35
·
answer #4
·
answered by catherine 2
·
0⤊
0⤋
(2x - 3)/4 - 3x/2 = 2x-18
2x - 3 - 6x = 8x - 72
-4x - 3 = 8x - 72
69 = 12x
x = 69/12
x = 23/4
2007-06-25 03:02:09
·
answer #5
·
answered by Becky M 4
·
0⤊
0⤋
let us see: ( 2x-3/4)-(3x/2)=2x-18 so 2x-3/4-6x/4=2x-18 so
-4x-3=8x-72 so 69=12x x=69/12
2007-06-25 03:22:39
·
answer #6
·
answered by golmangoly 1
·
0⤊
0⤋
(2x-3)/4 - 3x/2 = 2x - 18
Multiplying both sides of this equation by 4:
(2x - 3) - 4(3x/2) = 4(2x - 18)
2x - 3 - 6x = 8x - 72
-4x - 3 = 8x - 72
69 = 4x
x = 69/4
2007-06-25 02:59:02
·
answer #7
·
answered by MamaMia © 7
·
0⤊
3⤋
mamma mia after your
-4x - 3 = 8x - 72 step
12x=69
x=69/12
2007-06-25 03:01:58
·
answer #8
·
answered by Onur 1
·
0⤊
0⤋
Well,
i'm only in 7th grade,
but i'll try it......
wait whats x?????
:-o
hold on
gimme a sec
uummmm
x=.110????????????????????????
2007-06-25 03:04:23
·
answer #9
·
answered by Julie J 3
·
0⤊
0⤋